IMPACT OF GLYPHOSATE ON MICROBIAL ATTRIBUTES OF SOI L PLANTED WITH TWO SPECIES OF PASSION FRUIT - ERIKA VALENTE DE MEDEIROS; KRYSTAL DE ALCANTARA NOTARO; CIDNEY BARBOSA BEZERRA; ANTÔNIO RICARDO SANTOS DE ANDRADE; GUSTAVO PEREIRA DUDA (Revista Caatinga, 2014)
Glyphosate is one of best known agrochemicals and i s used to prevent the spread of weeds. However, little is known about the impact of this c hemical on non-target organisms such as the soil mi crobial community. Therefore, the objective of this study w as to evaluate the effect of glyphosate on the micr oorgan- ism population and the microbial attributes of soil s cultivated with yellow and sweet passion fruits. The experi- mental design used was complete randomized blocks i n a 3 x 2 factorial scheme with the times of soil s ample collection (0, 5 and 47 days after herbicide applic ation- DAH) and the two species of passion fruit ye llow ( Passiflorae dulis f. flavicarpa O. Deg.) and sweet ( Passiflora alata Dryand) as the factors,with three replica- tions. No impact of the glyphosate herbicide was fo undon the bacterial communities of soil. However, a mild and transitory impact was observedon the fungal pop ulations, encouraging these populationsat 47 DHA. G ly- phosate changed the carbon microbial biomass and so il microbial attributes, except for total organic c arbon. Multivariate, principal component analysis revealed that the total bacteria, endospore-forming bacteri a, total fungi, carbon microbial biomass and metabolic quoti ent attributes of soil are the most sensitive facto rs for pre- dicting the impact of glyphosate on biological indi cators of soil planted with two species of passion fruit yellow ( P. edulis f. Flavicarpa ) and sweet ( P. alata ).